Avaliação da produção e função surfactante de lactentes com bronquiolite viral aguda grave - Hartmann, Francine (2012)
Objectives: To evaluate surfactant production and function through lamellar body count (LBC) and stable microbubble test (LBC) in infants with severe bronchiolitis in mechanical ventilation. Design: Controlled cross-sectionalstudy. Setting: Pediatric intensive care unit. Local: unidade de terapia intensiva pediátrica. Patients: Twenty seven infants on mechanical ventilation, with ≤12 months of age were included in the study. Sixteen infants with the diagnosis of bronchiolitis. Eleven patients with normal lungs, submitted to surgery or another medical condition, without pneumopathy detected, were used as controls. Interventions: Lung fluid was collected during routine tracheal aspiration. Lamellar body count was performed in an automated cell counter. Tracheal samples were kept frozen at -20ºC until thawed for testing after 48 to 96 hours. At the moment of the analysis the samples were placed in a dithiothreitol solution (10mg/ml) at a ratio of 1 part of tracheal aspirate to 6 parts of the solution, vortexed for 10 seconds, and aspirated by the cell counter. All results were multiplied by 7. Stable microbubble test was performed in a blinded way according to the method described by Pattle et al. Measurements: Lamellar body count and stable microbubble test. Main Results:In the bronchiolitis group LBC was significantly lower than in the control group: median (interquartile range) 130,000 (61,250 362,250) lamellar bodies (LB)/μL vs. 609,000 (322,000 917,000) LB/μL; p=0.005. The SMT was also significantly lower in the bronchiolitis group: median (interquartile range) 10 (2 13) microbubbles (MBE)/mm2 vs. 304 (140 - 510) MBE/mm2; p<0.001. Conclusions: The data suggest that infants with bronchiolitis have reduced surfactant production and function. We speculate that these simple tests could be evaluated for the possibility to identify infants with bronchiolitis who will benefit from surfactant replacement therapy